Minimally processed ready-to-eat (RTE) Pomelo (Citrus maxima cv. Magallanes) segments at the point-of-sale in selected supermarkets and hypermarkets - Sermense, Yvone Noelle A. (College of Home Economics, University of the Philippines Diliman, 2014)
This study aimed to evaluate the physico-chemical, microbiological, and sensory qualities of minimally processed ready-to-eat (RTE) pomelo (Citrus maxima cv. Magallanes) segments procured from the point-of-sale in selected supermarkets and hypermarkets. The Magallanes segments were sampled from 6 test supermarkets and 2 test hypermarkets located in Quezon City and Marikina City, Philippines. Minimally processed RTE Magallanes pomelos were found to be sold in polystyrene trays covered with cling wrap, either in half-fruit (170-250 g) or whole-fruit (450-880 g) formats. The evaluated physico-chemical of the attributes of the pomelo segments included: titratable acidity; total soluble solids; color; water activity and moisture content. The Magallanes pomelo segments were found to be generally of acceptable maturity according to the established local and international maturity standards. The yeast and mold counts (YMC) ranged from 2.06 log CFU/g to 4.05 log CFU/g, and were found to be within acceptable limits. The total coliform counts (TCC) of the samples generally exceeded the recommended limits, with values reaching up to >4.00 log MPN/g. Salmonella spp. per 25 g sample was also detected in one supermarket sample. Possible microbial contamination during minimal processing of the Magallanes pomelos could have caused the high TCC levels and the presence of Salmonella spp. The pomelos in retail were described to be slightly firm and juicy, but neutral in pink color, flavor and taste. Hypermarkets were shown to generally sell minimally processed RTE Magallanes pomelo segments with better physico-chemical, microbiological and sensory qualities than the supermarkets. More focus on the evaluation of the microbiological aspect of pomelos sold in retail should be done in future studies to ensure its wholesomeness.